Theory of mind deficit in people with schizophrenia during remission - HEROLD, R.; TÉNYI, T.; LÉNÁRD, K.; TRIXLER, M. (Psychological medicine, 2002)
Background. The authors' goal was to investigate the presence or absence of theory of mind impairments among people with schizophrenia during remission. Recent research results interpret theory of mind deficits as state rather than trait characteristics, connecting these impairments mainly to the acute episode of psychosis. Methods. Twenty patients with schizophrenia in remission and 20 matched control subjects were evaluated. Participants were presented with one first-order theory of mind task, one second-order theory of mind task, two metaphor and two irony tasks adapted from previous studies. Results. The schizophrenic patients performed a statistically significant impairment in the irony task, as there were no significant differences in the cases of the other evaluated tasks. Conclusions. These preliminary results suggest that theory of mind impairments can be detected not only in the acute phase as found in previous research studies, but also in remission.